Evaluasi Manajemen Program Pengelolaan Penyakit Kronis (Prolanis) Dalam Meningkatkan Kualitas Pelayanan BPJS Kesehatan Di Puskesmas Singgani Kota Palu - Yuliarni, Indah; Komara, Endang; Handayani, Nining (ManBiz: Journal of Management and Business, 2025)
Non-Communicable Diseases (NCDs), such as hypertension and diabetes mellitus, have become an increasingly significant global health threat, including in Palu City. To address this, the Chronic Disease Management Program (Prolanis), initiated by BPJS Kesehatan, aims to improve the quality of life for individuals with NCDs. This study employs Darmawan's (2019) program evaluation theory, which encompasses input, process, and output components. The objective of this research is to evaluate the management of Prolanis in improving the quality of BPJS Kesehatan services at Singgani Public Health Center (Puskesmas) in Palu City. The research method used is qualitative with a case study approach, utilizing interviews, observations, and various related documents. The findings reveal that, in terms of input, human resources are inadequate, financial resources are highly limited, materials are unavailable, but the methods align with the Standard Operating Procedures (SOP). Regarding the process, planning has been conducted according to procedures, organizing is disrupted, actuating has not been implemented effectively, and controlling is carried out by the responsible parties. As for the output, some participants have not consistently attended activities but remain within the safe category.